EVALUASI PENERAPAN SISTEM PENGENDALIAN MANAJEMEN DALAM MENINGKATKAN KINERJA PERUSAHAAN PADA PT JAYA BITUNG MANDIRI - Rotinsulu, Shintya Ulfa; Runtu, Treesje; Mintalangi, Syermi S.E (Universitas Sam Ratulangi, 2021)
A management control system is a system used to encourage members to implement each strategy effectively and efficiently to achieve company goals. The purpose of this study was to determine how the application of management control systems in improving company performance at PT Jaya Bitung Mandiri. The data analysis method used is qualitative research with a descriptive approach. The results showed that the management control system at PT Jaya Bitung Mandiri was running well. This is evidenced by indicators of organizing, policies, planning, recording or accounting, reporting, that have been running quite effectively and are able to improve company performance as assessed by the company's revenue and net profit which has increased over the past 3 years. . As a matter of consideration, companies should pay more attention to unfulfilled factors in the management control system so that company management will be more effective and efficient.